Nilai-nilai Pendidikan Karakter Tema Hidup Rukun pada Buku Siswa di Sekolah Dasar - Khairani, Annisa; Ain, Siti Quratul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to analyze and describe the character values ​​contained in the 2013 curriculum integrative thematic book published by the Ministry of Education and Culture. The data and data sources in this study are the second-grade students' books with the theme "Life in harmony." The data collection technique in this research uses unstructured interviews and the observation method with note-taking techniques. The data collected is then analyzed. The data analysis technique used is the Milles and Huberman model, with the stages of data reduction, data presentation, and drawing conclusions. Based on the results of the study, the second-grade student's book on the theme of living in harmony already contains the expected character values. A total of 109 character values ​​were found from the five values ​​carried out in this study. The order of character values ​​found from the lowest to the highest is nationalism values ​​totaling 14 values. Independent values ​​have as many as 18 values, mutual cooperation values ​​as many as 23 values, religious values ​​as many as 24 values, and the last one that most often appears is the integrity value, as many as 30 values.